MODERN APPROACH TO HEMOCOLITIS SYNDROME IN CHILDREN - Худайбердиева Чарос Курдашевна (Web of Journals Publishing, 2026)
The article analyzes the etiology, pathogenesis, risk factors and preventive measures of acute diarrhea in children with acute diarrhea with hemocolitis syndrome. The disease has a high incidence among children under 5 years of age, causing dehydration and severe complications. Based on the analysis of the literature, the importance of hygiene, proper nutrition, breastfeeding, safe drinking water, sanitation and vaccination was highlighted. The etiological factor of hemocolitis was confirmed in the laboratory using the PCR method. In order to assess the clinical and laboratory indicators of acute diarrhea with hemocolitis syndrome in young children, which was one of the objectives of the study, we divided 120 children included in the study into severity levels using the Clark scale and conducted a comparative analysis of the clinical features of the disease according to the etiological factor of hemocolitis syndrome and severity level.
Keywords: Hemocolitis syndrome, children, prevention, dehydration, rotavirus, etiology.